The Abundance of Microplastics in Gastropods in The Molas Waters of North Sulawesi - Nadia I. Khoirunnisa; Nickson J. Kawung; Natalie D. C. Rumampuk; Elvy L. Ginting; N. Gustaf F. Mamangkey; Jane M. Mamuaja (Sam Ratulangi University, 2025)
Marine debris is a global problem faced by many countries. One of the most common types of waste found in marine environments is plastic. Plastic takes about 200–1000 years to fragment without being completely degraded. In aquatic environments, plastics are exposed to ultraviolet rays, causing degradation and breaking down into smaller sizes known as microplastics. Microplastics are particles less than 5 mm in size derived from the breakdown of larger plastics. The types of microplastics include film, fiber, fragment, granule, and foam. Microplastics can enter gastropods through contaminated water or sediments. This study aims to identify the types and abundance of microplastics in gastropods. Samples were collected in Molas Waters at two different times, July 2024 and April 2025, using the roaming method. The gastropods sampled were Tylothais sp. and Terebralia sp.. The results showed that in July 2024, the number of microplastics was 3.05 particles/20 individuals, while in April 2025 it decreased to 2.2 particles/20 individuals. There was a difference in abundance between the two species, where in July 2024 Tylothais sp. had the highest number, whereas in April 2025 Terebralia sp. showed the highest. The most common type of microplastic found was fiber. Keywords: plastic, mikroplastic, particle, gastropod, abundance Abstrak Sampah laut merupakan masalah global yang dihadapi banyak negara. Salah satu jenis sampah yang paling sering ditemukan di perairan adalah plastik. Plastik membutuhkan waktu 200–1000 tahun untuk terpecah tanpa bisa benar-benar terurai. Di perairan, plastik terpapar sinar ultraviolet sehingga mengalami degradasi dan berubah menjadi ukuran lebih kecil yang dikenal sebagai mikroplastik. Mikroplastik adalah partikel berukuran kurang dari 5 mm yang berasal dari pecahan plastik lebih besar. Jenis mikroplastik meliputi film, fiber, fragmen, granul, dan foam. Mikroplastik dapat masuk ke tubuh gastropoda melalui air maupun sedimen yang terkontaminasi. Penelitian ini bertujuan untuk mengetahui jenis dan kelimpahan mikroplastik pada gastropoda. Sampel diambil di Perairan Molas pada dua waktu berbeda, yaitu Juli 2024 dan April 2025, menggunakan metode jelajah. Gastropoda yang dijadikan sampel adalah Tylothais sp. dan Terebralia sp.. Hasil analisis menunjukkan pada Juli 2024 jumlah mikroplastik sebesar 3,05 partikel/20 individu, sedangkan pada April 2025 turun menjadi 2,2 partikel/20 individu. Terdapat perbedaan kelimpahan antara kedua spesies, di mana pada Juli 2024 Tylothais sp. memiliki jumlah tertinggi, sedangkan pada April 2025 tertinggi terdapat pada Terebralia sp.. Jenis mikroplastik yang paling banyak ditemukan adalah fiber. Kata kunci: plastik, mikroplastik, partikel, gastropoda, kelimpahan